Isotherm Of Medicinal Plants - Sultanova Sh.A., Safarov J.E., Aït-Kaddour А., Jumayev B.M. (International Journal of Advanced Science and Technology, 2020)
The sorption and desorption of medicinal plants was carried out on a vacuum installation with mercury gates and McBan quartz scales. The measurements were carried out at 293 K and a residual air pressure of 10-3-10-4 Pa. We studied the sorption and desorption of water vapor at 293 K for medicinal forestry plants - peppermint (Mentha), nettle (Urtica), plantain (Plantago) and zizifora (Ziziphora). The characteristics of the processes of sorption and desorption of medicinal plants were studied: it was found that the specific surface area of the capillaries is 137.26 m2/g, and the total pore volume for zisphora under convective drying is 0.095 cm3/g. For plantain, the characteristics of sorption and desorption were revealed: the confirmed specific surface of the capillaries is 92.10 m2/g, while the total pore volume is 0.250 cm3/g